Transcriptome profiles of high-lysine adaptation reveal insights into osmotic stress response in Corynebacterium glutamicum - Wang, Jian; Yang, Jian; Shi, Guoxin; Li, Weidong; Ju, Yun; Wei, Liang; Liu, Jun; Xu, Ning (Frontiers in Bioengineering and Biotechnology, 2022)
Corynebacterium glutamicum has been widely and effectively used for fermentative production of L-lysine at the industrial scale. However, the high-level accumulation of end-products will inevitably lead to osmotic stress and hinders further increase of L-lysine production. At present, the underlying mechanism by which C. glutamicum cells adapt to high-lysine induced osmotic stress is still unclear. In this study, we conducted comparative transcriptomic analysis by RNA-seq to determine gene expression profiles under different high-lysine stress conditions. The results indicated that the increased expression of some metabolic pathways such as sulfur metabolism, and specific amino acid biosynthesis might offer favorable benefits for high-lysine adaptation. Functional assays of 15 representative differentially-expressed genes showed that the enhanced expression of multiple candidate genes especially grpE chaperon conferred high-lysine stress tolerance in C. glutamicum. Moreover, DNA repair component MutT and energy-transducing NADH dehydrogenase Ndh were also found to be important for protecting cells against high-lysine induced osmotic stress. Taken together, these above findings will provide broader views of transcriptome profiles and promising candidate targets of C. glutamicum for the adaptation of high-lysine stress during fermentation.